FAKTOR SOSIAL DAN EKONOMI YANG MEMPENGARUHI PROBABILITAS PENGGUNAAN ALAT KONTRASEPSI DI DESA KESIMAN KERTALANGU - Apriani, Anak Agung Rai Inten; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 5 No 6 (2021): VOL 10 NO 6, JUNI 2021 [2223 - 2660], 2021)
The implementation of the family planning program is marked by the use of contraceptives or methods of family planning for women of childbearing age. The purpose of this study was to analyze the effect of education level, family income level, and the number of children simultaneously and partially owned on the probability of using contraceptives (KB) in fertile aged couples in Kesiman Kertalangu Village. This research was conducted in Kesiman Kertalangu Village. The number of samples taken was 95 couples of childbearing age aged 15-49 years with the status of being married and having children using the Non-Probability Sampling method, especially the purposive sampling technique. The data were collected by means of observation and structured interviews which were then analyzed using logistic regression analysis techniques. The results showed that the level of education, the level of family income and the number of children owned had a simultaneous and significant effect on the probability of using contraceptives in Kesiman Kertalangu Village. Partially, the level of education, the level of family income and the number of children owned have a positive and significant effect on the probability of using contraceptives in the village of Kesiman Kertalangu.   Keyword : Contraception, Education, Family Income, Number of Children